Heterostructure CoS/NC@MoS2 Hollow Spheres for High‐Performance Hydrogen Evolution Reactions and Lithium‐ION Batteries. Issue 24 (5th November 2018) - Zhao, Yueying; Bi, Mengfan; Qian, Fangfang; Zeng, Peiyuan; Chen, Mengna; Wang, Ruojie; Liu, Yangyang; Ding, Yang; Fang, Zhen
Abstract: Uniquely structured CoS/N‐doped carbon@MoS2 (denoted as CoS/NC@MoS2 ) hollow spheres were successfully synthesized by using a well‐designed N‐rich Co‐metal organic framework (ZIF‐67) precursor and template. Owing to the good mechanical stability and conductivity of carbon hollow spheres, N‐doped carbon, and Co−Mo bonds, the as‐prepared CoS/NC@MoS2 composites exhibit outstanding electrochemical performance both in electrocatalytic and energy storage applications. An overpotential of 77 mV at 10 mA cm −2, and a Tafel slope of 67 mV dec −1 could be obtained in acid environment for the hydrogen evolution reaction. As an anode material for lithium‐ion batteries, the as‐prepared composites exhibit good cycling stability with a high reversible specific capacity of 802.4 mA h g −1 at a current density of 1 A g −1 after 400 cycles and good rate capability. Abstract : Time to evolve : CoS/NC@MoS2 hollow spheres show outstanding electrocatalytic hydrogen evolution properties and good cycling stability as the anode for lithium‐ion batteries.